Producing Bodies, Knowledge, and Community in Everyday Civilian Struggle over Surveillance - Billies, Michelle C. (2013)
In a global context of rapidly expanding security practices, those cast as social threats are themselves often most risk of harm. In this dissertation, I develop the concept surveillance threat (ST) to describe the perception or experience of impending or actual harm faced by targeted civilians when they are stopped or screened by law enforcement. Singled out by race and other lines of sociocultural force, those stopped risk physical, legal, sexual, and spatial consequences. Yet focusing solely on the risk of harm limits the full meaning of this encounter. As I show in my research, civilians persistently struggle against these threats. Using the police practice of stop and frisk in New York City as a case study, I analyze ST and civilian response from the civilian perspective. In my mixed methods approach, I bring together survey and narrative data on stop and frisk, widening the unit of analysis from unidirectional harm to multidirectional struggle. Shifting attention to the interaction as a dynamic reframes these relations of power as more than a simple, imbalanced opposition. Instead, based on my findings, I theorize an embodied civilian psychology of responsiveness to threat that enables those targeted to engage the encounter as an active site of conflict. I find civilians consistently claim their rights, protect themselves and others, assert social power, construct critical knowledge, and pursue justice. Applying Abu Lughod's (1990) insight where there is resistance, there is power, I then study how civilians enact urban civil life through their interactions with police, recognizing a collective imaginary civilians draw on to influence the conditions of their daily lives. With concern for the ways police practice is restructuring urban environments by enforcing particular raced sexualities and genders, I bring a special focus to civilian constructions of racialized, sexual, and gender-infused space